Enhancing medication appropriateness: Insights from the STOPP (Screening Tool of Older Persons’ Prescriptions) criteria version 3 on prescribing practices among the older adults in Pakistan - Sadia, Halima; Naveed, Safila; Rehman, Hina; Jamshed, Shazia; Dilshad, Huma (Frontiers in Pharmacology, 2025)
BackgroundThe prevalence of potentially inappropriate medications (PIMs) in older adults populations is a significant concern, often leading to adverse drug events and increased health-care utilization.ObjectiveIn the present study, we aim to evaluate the prevalence of PIMs among hospitalized older adults patients in Pakistan using STOPP (Screening Tool of Older Persons’ Prescriptions) criteria version 3.MethodologyA prospective observational study was conducted at a tertiary-care hospital in Karachi over 1 year from March 2023 to March 2024. Patients aged 60 years and above, prescribed at least one medication, were included. Data on demographics, comorbidities, and medications were collected and analyzed using the STOPP criteria to identify PIMs. Statistical analysis was performed using IBM SPSS Statistics version 21. To find the variables linked to PIM use, multivariable logistic regression analysis was used. The 95% CI and adjusted odds ratio (aOR) were used to measure the statistical association’s strength. A p-value of less than 0.05 was deemed statistically significant.ResultsAmong 450 participants, the median age was 67 years, with a predominance of male patients (55.3%). The prevalence of PIM use was 56.6%, and a total of 388 instances of PIM use were identified according to STOPP criteria version 3. Acetylsalicylic acid (18%) and pheniramine (11%) were the most frequent inappropriately prescribed medications. The multivariable logistic regression analysis revealed that polypharmacy and the presence of one or more comorbidities primarily influence the PIM use.ConclusionThe findings highlight a critical need for improved prescribing practices in the older adults population in Pakistan. Utilizing screening tools like the STOPP criteria can significantly enhance medication safety and optimize pharmacotherapy in this vulnerable group.